Investigating the Effect of Drought Stress on Growth and distribution of Purple Nutsedge (Cyperus rotundus L.) - N. Karimi Arpanahi; S.V. Eslami; R. Dehghan Khalili (Majallah-i ḥifāẓat-i giyāhān, 2017)
Introduction: Drought is one of the most important and common environmental stresses in the country, which affect different stages of plant growth and development. Drought can affect plants growth in various ways, thereby reduces and delays germination, and decreases shoot growth and dry matter production. In the case of high water stress, it results showed great reductions in photosynthesis and disruption of the physiological processes, as well as growth stop and eventually plant death.Purple nutsedge (Cyperus rotundus L.) has been listed as the world’s worst weed based onits worldwide distribution (92 countries) and interference with over 50 crops. It causes high yield losses in fruiting vegetables and cucurbits in eastern and southeastern parts of Iran, where drought stress is a common phenomenon. Therefore, it is of utmost importance to understand the response of this noxious weed species to drought stress. Materials and Methods: In order to study the effect of drought stress on growth and distribution of purple nutsedge, two separate experiments were carried out in a randomized complete block design with three replications in the Research Greenhouse at Birjand University in 2013. The first experiment consisted of 6 irrigation interval levels (3, 6, 9, 12, 15 and 18- day irrigation intervals) and the second one were 5 irrigation levels based on field capacity (12.5, 25, 50, 75 and 100 % FC). Results and Discussion: ANOVA results of both experiments showed that all growth characteristics of purple nutsedge were affected by drought stress. The results of irrigation interval stress experiment showed that the maximum height (76 cm), leaf area (110.83 cm2), stem number (4.66 stemperpot), shoot dry weight (4.132 gr per plant), tuber number (7.66 tuber per pot) and total underground organs dry weight (4.435 gr per plant) were observed in 3- day irrigation interval. Also, the lowest amount of these characteristics was obtained in 18- day irrigation interval. The influence of increasing the irrigation intervals up to 18 days was obvious in reducing weed morphological characteristics. With longer irrigation intervals, weed height declined severely, and the greatest reduction in plant height (62.43% comparison to control) was obtained from 18- day irrigation interval. Irrigating plants at 12, 15 and 18- day intervals decreased 66.15, 77.84 and 88.96% in weed leaf area compared to 3- day irrigation interval (control), respectively. The maximum reduction in stem number (78.54% relative to control) was observed at 18- day irrigation interval. Increasing drought stress levels significantly decreased 62.95, 76.27, 97.57% shoot dry weight under 12, 15 and 18- day irrigation intervals regimes, respectively. . Also, increaseddrought levels, significantly reduced weed tuber number, so that no tuber produced at 18- day irrigation interval. Moreover, underground organs dry weight decreased 51.91, 65.68 and 88.48% at 12, 15 and 18- day irrigation intervals compared to control, respectively. In other experiment, the maximum height (70.33 cm), leaf area (116.33 cm2), stem number (7 stem per pot), shoot dry weight (3.701 gr per plant), tuber number (5.66 tuber per pot) and total dry weight of underground organs (513/3 gr per plant) were obtaind at 100% field capacity (control).. The results showed that plant height decreased with increasing drought levels, so the minimum plant height was observed at 25 and 12.5% FC. Increasing drought stress reduced leaf area 68.59 and 91.61% at 75% and 50% FC compared to control, respectively. The maximum reduction in stem number was observed at 25 and 12.5% FC. The weed dry matter decreased 52.90 and 88.05% compared to control at 75 and 50% FC, respectively. Tuber production was severely affected by soil water content reduction, so that no tuber was produced at 25 and 12.5% FC. Dry weight of underground organs in purpule nutsedge decreased 39.48 and 79.24% at 75 and 50% FC compared to control, respectively. Conclusion: Overall different levels of drought stress in both experiments, were reduced all weed growth characteristics. Since reproductive organs such as tuber and rhizome were not produced at 18- day irrigation interval regime and 25 and 12.5% FC,, therefore it seems non-chemical control methods such as irrigation management can be effective to control this weed. Obviously repeating this research in field conditions is required to confirm these results.